Performance analysis of highly improved hybrid turbo codes for 4G wireless networks - Jose Raj, M.; Sharmini Enoch, Dr. (International Journal of Engineering and Technology, 2019)
Efficient error correcting codes are essential in modern digital communication systems. Highly Improved Hybrid Turbo Code (HIHTC) is a low complex error and efficient error correcting code with excellentBit Error Rate (BER) which is comparable to Low Complexity Hybrid Turbo Codes (LCHTC), Improved Low Complexity Hybrid Turbo Codes (ILCHTC) and other Hybrid Turbo Codes. Rate 1/3 HIHTC shows a BER of 10-5 for E b/No of 1.7 dB which is closer to the E b/No of Improved Low Complexity Hybrid Turbo Codes. In this paper we analyze the performance of HIHTC in comparison with otherLow Complexity Hybrid Turbo Codes, for their performance in 4G and 5G wireless networksÂ Â